Analysis System Of Attendance Using Radio Frequency Identification (RFID) - Lestari A P; Ariani F (Bandar Lampung University (UBL), 2017)
College in London has been quite a lot, of course, we've all been know it that universities are places of learning activities that must be met by the student, faculty and staff of the college course requires attendance Students, faculty and staff as proof of attendance. Attendance system that is still used manually, which certainly has many short comings example: first waste paper and require many spending on paper, the two students one sign column of the signing, the three professors forgot to bring or put absent so that, absent are not carried away by the lecturers teacher.